Tinjauan Pelaksanaan Penyusutan dan Pemusnahan Rekam Medis di RSUD Muntilan - Hanifah Shofiarini; Makhrum Irmaningsih; Dyah Megawati Surip Solekhah; Adinda Dwi Nurul ’Ain; Esa Maheswari; Marko Ferdian Salim; Emi Nugroho; Bagus Setyadi (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Medical records are crucial documents in a hospital's patient care. Long-term use of paper-based or conventional medical records might result in issues including misfiles, disorganized shelves, and limited storage space. As a result, it's important to implement a procedure for the retention, elimination, and destruction of medical record files in order to eliminate useless files, decrease the growth in the number of files, and maintain the standard of medical record services. This study aims to evaluate the 5 M (Man, Money, Method, Material, and Machine) components of the process of eliminating and destroying medical record files at RSUD Muntilan. The object of research is medical record files, storage facilities, storage, implementation, and destruction of medical files. The method used in this study is a qualitative method through data collection by observation and interviews with medical record officers. The research was carried out at the Muntilan Hospital from June to July 2022. Based on the research that has been done, the process of implementing and destroying medical records is in accordance with applicable procedures and the regulation of the Ministry of Health No. 269 of 2008.